The Effectiveness of Distance Teaching and Learning Activities in Primary Schools - Riyanto, Yayan; Nandiyanto, Asep Bayu Dani; Muhammad, Nazeri (Indonesian Journal of Multidiciplinary Research, 2021)
Learning is an activity to gain useful knowledge. The time to study is not limited, we have to learn from the moment we are born. Elementary school children are those with elementary age, namely 6-12 years, this period is commonly referred to as the intellectual period. The Covid-19 pandemic has disrupted activities so that all activities require a revolution. Technology plays an important role in distance teaching and learning activities such as the use of social media or educational-based applications that make teaching and learning activities supposed to work. The method used is descriptive method. The purpose of this study is to find out about distance learning in elementary schools which is still being asked whether it is effective or not, so it raises the question whether students are well educated at basic age is very important for the foundation of character and talent.